The Images in “Maleficent” Novel by Elizabeth Rudnick - Nommariati Purba; Ambalegin Ambalegin (Linguistic, English Education and Art (LEEA) Journal, 2020)
This study aims to analyze the images found in the novel Maleficent by Elizabeth Rudnick in 2014. This is a descriptive qualitative study. The method of data collection is by observation (reading) and note taking (underlining). The result of the analysis is to find out the nine archetypal images. The images are water (river), sun, colors (red, green, blue, black, white), serpent, number (three), good mothers, wise old man, garden, and tree. The images are able to enlighten the fantasy moment created by the writer and bring the readers’ experiences to the literary work of fantacy. Keywords: Archetypal Image, Maleficent, Novel